2016
DOI: 10.1186/s40781-016-0104-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding high fat diet to beef cattle on manure composition and gaseous emission from a feedlot pen surface

Abstract: BackgroundDietary manipulation is a common practice to mitigate gaseous emission from livestock production facilities, and the variation of fat level in the diet has shown great influence on ruminal volatile fatty acids (VFA) and enteric methane generation. The changes in dietary fat levels influence rumen chemistry that could modify manure nutrient composition along with odor and gaseous emissions from manure management facilities.MethodsA field experiment was carried out on beef cattle feedlots to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…Similar results were observed in common carp (Cyprinus carpio L.) and meagre (Argyrosomus regius) [30,31]. The high-fat content in the feed exceeding the physiological requirements of the animal may cause a digestive disturbance, reduction in feed intake, and downregulation of the absorption and utilization of nutrients, which ultimately results in growth performance impairment [32][33][34]. In the current study, we observed that the bile acid supplementation could effectively alleviate the negative effects of a high-fat diet in common carp.…”
Section: Discussionsupporting
confidence: 60%
“…Similar results were observed in common carp (Cyprinus carpio L.) and meagre (Argyrosomus regius) [30,31]. The high-fat content in the feed exceeding the physiological requirements of the animal may cause a digestive disturbance, reduction in feed intake, and downregulation of the absorption and utilization of nutrients, which ultimately results in growth performance impairment [32][33][34]. In the current study, we observed that the bile acid supplementation could effectively alleviate the negative effects of a high-fat diet in common carp.…”
Section: Discussionsupporting
confidence: 60%
“…It is also reported that aerobicanaerobic condition changes in pH, and organic matter influence the solubility of P forms [22]. Cattle fed diets containing the highest concentration of P also produced manure with the highest concentration of total P [22], but cattle fed on high fat have no impact on manure composition [24].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it was the aim of this study to investigate for the first time the effect of selected pure chemicals, representing relevant constituents of manure [ 41 , 42 , 43 , 44 , 45 ], on the soil sorption of PhACs. This was done by using urea and potassium dihydrogen phosphate (KH 2 PO 4 ) as major nutrient components, acetic acid and phenol as representatives of volatile organic compounds, and nonadecanoic acid (C:19) as a non-polar organic constituent of manure.…”
Section: Introductionmentioning
confidence: 99%